Nickel-based nanomaterials: a comprehensive analysis of risk assessment, toxicity mechanisms, and future strategies for health risk prevention - Xiaoting Zhou; Jiaqi Liao; Zipeng Lei; Huiqin Yao; Le Zhao; Chun Yang; Yan Zu; Yuliang Zhao (Journal of Nanobiotechnology)
Abstract Nickel-based nanomaterials (NBNs) have seen a surge in usage across a variety of applications. However, the widespread use of NBNs has led to increased human exposure, raising questions about their associated health risks, both in the short and long term. Additionally, the spread of NBNs in the environment has attracted considerable attention, emerging as a vital focus for research and development. This review aims to provide an in-depth assessment of the current understanding of NBNs toxicity, the mechanisms underlying their toxicological effects, and the strategies for mitigating associated health risks. We begin by examining the physicochemical properties of NBNs, such as particle size, composition and surface functionalization, which are key determinants of their biological interactions and toxicity. Then, through an extensive analysis of in vitro and in vivo studies, we highlight the adverse effects of NBNs exposure, including the generation of reactive oxygen species (ROS), oxidative stress, inflammation, cytotoxicity, genotoxicity, and immunotoxicity. To address the potential health risks associated with NBNs, we propose future strategies for risk prevention, including the development of safer nanomaterial designs, implementation of stringent regulatory guidelines, and advancement of novel toxicity testing approaches. Graphical Abstract